Evaluation of Sclerotium rolfsii as mycoherbicide for Parthenium: Factors affecting viability and virulence - and S.K. HASIJA, JYOTI MISHRA, A.K. PANDEY (Indian Phytopathology, 2002)
Mature sclerotia of 2 isolates (SR1 & SR2) of S. rolfsii [Corticium rolfsii] were stored at 5 different temp. (0, 10, 20, 30 and 40degC+-2degC), 5 RHs (0, 25, 50, 75 and 100%) and 4 formulations (sterilized and unsterilized soil, unformulated and host debris). Viability and virulence against Parthenium seedings (3-4 leaves stage) was determined over a period of 24 months. Sclerotia survived longest and remained virulent at lower levels of RH (0-25%) and temp. (0-20degC+-2degC) when stored with host debris insterilized soil. Higher temp., RH and unsterilized soil formulation did not favour the organism.